DYNAMICS AND CURRENT STATE OF YOUTH CRIME IN THE REPUBLIC OF UZBEKISTAN - Uralov Sarbon Sardorovich (Scholar Express Journals, 2024)
The dynamics of crime is the increase or decrease of crime in general and its structural indicators within a certain period (month, quarter, half-year, year, five-year, ten-year, twenty-year, etc.). Many factors influence the dynamics of crime. The most important of them can be grouped into two groups: social factors and legal factors.
Keywords: dynamics; factors; crime; general